2023
DOI: 10.3390/ijerph20043661
|View full text |Cite
|
Sign up to set email alerts
|

Indian Healthcare Workers’ Issues, Challenges, and Coping Strategies during the COVID-19 Pandemic: A Cross-Sectional Study

Abstract: India faced the maximum number of mortalities and morbidities during the second wave of COVID-19. Healthcare workers (HCWs) worked in high-pressure and stressful environments. Therefore, this study aimed to assess the common issues, challenges, and coping strategies of HCWs, as well as the statistical association between demographical characteristics and coping strategies. A cross-sectional study was conducted with 759 HCWs, involving simple, random sampling in Rajasthan, India, between August 2022 and October… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…This suggests that the association between marital status and psychological impact extends beyond regional boundaries. Additionally, studies conducted in Turkey (67) and India (68) showed that higher educational qualifications are associated with better psychological well-being and coping mechanisms among HCWs, aligning with the findings of this study.…”
Section: Alsupporting
confidence: 90%
“…This suggests that the association between marital status and psychological impact extends beyond regional boundaries. Additionally, studies conducted in Turkey (67) and India (68) showed that higher educational qualifications are associated with better psychological well-being and coping mechanisms among HCWs, aligning with the findings of this study.…”
Section: Alsupporting
confidence: 90%
“…Indian HCWs worked in high-pressure and stressful environments, due to which those working in COVID-19-designated hospitals reported clinically significant depression and poor sleep [28]. A study done in India has also shown similar findings where sleep-deprived HCWs working during this pandemic have been pushed for stress, mental health illness, and non-adaptive coping strategies [29,30]. A study done in Italy among healthcare professionals attributed sleep disturbances to psychological stress and women were at more risk.…”
Section: Discussionmentioning
confidence: 90%
“…Community-level challenges were reported by 11 studies (47.5%) conducted in Africa ( n = 3, 27.25%), India ( n = 3, 27.25%), Bangladesh ( n = 1, 9.1%), Nigeria ( n = 1, 9.1%), Pakistan ( n = 1, 9.1%), South Korea ( n = 1, 9.1%), and Turkey ( n = 1, 9.1%). Challenges included mainly poor societal support (e.g., community members did not recognize HCWs’ contribution during the pandemic) and stigma, isolation and discrimination from society as they had to work in COVID-19 wards, and community members feared that they will contract COVID-19 from HCWs [ 33 , 36 , 38 40 , 42 , 45 , 64 – 66 , 70 ]. Needs were reported by two studies (18.2%) with HCWs reporting support provided by the society by recognizing their contribution in providing support to people and following public protocols for controlling the spread of COVID-19 so as to reduce the burden on them [ 36 , 38 ].…”
Section: Resultsmentioning
confidence: 99%